Impact of aspirin on the prognosis in patients with coronary spasm without significant atherosclerotic stenosis. (1st October 2016) - Ishii, Masanobu; Kaikita, Koichi; Sato, Koji; Yamanaga, Kenshi; Miyazaki, Takashi; Akasaka, Tomonori; Tabata, Noriaki; Arima, Yuichiro; Sueta, Daisuke; Sakamoto, Kenji; Yamamoto, Eiichiro; Tsujita, Kenichi; et al.
Abstract: Background: Coronary spasm is one of the mechanisms of myocardial infarction with nonobstructive coronary arteries (MINOCA). The aim of this study was to investigate the effects of aspirin on future cardiovascular events in patients with coronary vasospastic angina (VSA) with non-significant atherosclerotic stenosis. Methods: This was the retrospective analysis of the 640 VSA patients with non-significant atherosclerotic stenosis (≤ 50% stenosis) among 1, 877 consecutive patients who underwent acetylcholine (ACh)-provocation testing between January 1991 and December 2010. The patients were divided into 2 groups treated with ( n = 137) or without ( n = 503) low-dose aspirin (81–100 mg/day). We evaluated major adverse cardiac events (MACE), defined as cardiac death, nonfatal myocardial infarction, and unstable angina. Results: In the study population, 24 patients (3.8%) experienced MACE; there were 6 cases in VSA patients with aspirin and 6 in those without aspirin. Multivariate Cox hazards analysis for correlated factors of MACE indicated that use of statin (HR: 0.11; 95% CI: 0.02 to 0.84; P = 0.033), ST-segment elevation during attack (HR: 5.28; 95% CI: 2.19–12.7; P < 0.001), but not the use of aspirin as a significant predictor of MACE. After propensity score matching ( n = 112, each), Kaplan–Meier survival analysis indicated almost identical rate of 5-year survival free from MACE in those with aspirin, compared to those without aspirin in the entire and matched cohort ( P = 0.640 and P = 0.541, respectively). Conclusions: Low-dose aspirin might not reduce future cardiovascular events in VSA patients with non-significant stenosis.